PELATIHAN ORGANISASI DOKUMEN UNTUK MENDUKUNG EFEKTIVITAS WORK FROM HOME (WFH) PADA DEPOK CREATIVE WOMAN - Marie, Iveline Anne; Adisuwiryo, Sucipto; Witonohadi, Amal; Najih, Muhammad; Caesar, Marcel Patulus (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2023)
The impact of the Covid-19 Pandemic has resulted in changes in lifestyle and activities. This is also felt by entrepreneurs who are members of Depok Creative Woman and partners in the Community Service Program. The problems faced by partners are how to use information technology and Google Drive, which can be used to create and store documents that can be accessed and edited online together in WFH situations, how to create and distribute questionnaires that can be used online, what are the security factors that need to be considered in the use of information technology online, as well as how to use information technology in offline internet conditions. This activity aims to provide training on organizing documents to support the effectiveness of WFH activities for partners. The activity plan begins with the identification of partner problems. Next, the activity team is coordinated to find solutions to problems and assignments by team members. Implementation of activities utilizes the video conference Zoom application to explain and practice partners how to utilize information technology related to organizing documents to support the effectiveness of WFH activities. Based on the results of 18 respondents, it is known that 100% of respondents stated that training on uploading documents to Google Drive was beneficial for small and medium businesses/business activities.